Pengaruh Pertumbuhan Industri Pariwisata Dan Indeks Pembangunan Manusia Terhadap Disparitas Pendapatan di Kota Surabaya - Moh Toriq Alfian; Muhammad Yasin (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
The city of Surabaya, as one of the cities in East Java Province, is active in the tourism sector. However, for many of them there are still income disparities in this metropolitan city. In tourism, there are several indicators that need to be paid attention to, namely the number of tourist visits, the number of hotels and the GRDP of the tourism sector. These three are appropriate benchmarks in approaching the growth of the tourism industry. Not only that, the human development index is also an important point for measuring the level of human welfare so that large disparities do not occur. This research aims to determine the influence of the growth of the tourism industry and the human development index on income inequality in the city of Surabaya. The type of research used is descriptive quantitative using secondary data obtained from the Department of Culture, Youth and Sports and Tourism of the City of Surabaya and the Central Statistics Agency of the City of Surabaya. The data obtained from 2014 - 2023 was processed using a time series method and then tabulated and analyzed using SPSS version 25. The results obtained from the F test for the two independent variables had a significant effect on income inequality. In the t test, partially the tourism industry growth variable has a positive and significant effect on income inequality, then the human development index variable has a negative and significant effect on income inequality in the city of Surabaya.